Optimization of Public Services through It-Based Drilling Well Mapping in Tasikmalaya Regency - Setiadi, Ade Setiadi; Kania, Ikeu; Ulumudin, Aceng (Yayasan Ilomata, 2025)
Tasikmalaya Regency faces significant obstacles in the provision of clean water, especially in areas that are prone to drought during the dry season. Although the central and provincial governments have provided assistance in the form of drilled wells, until now there is no integrated data collection system available to map the exact location of drilled wells. This research aims to create innovations in public services related to the provision of clean water by developing information technology-based drilled well mapping (Deep Well Map) so that groundwater management can be carried out more efficiently. This study applies a qualitative descriptive method with data collection techniques through direct observation, interviews with village heads in 11 villages receiving drilled well assistance, and data triangulation to ensure the accuracy of the information collected. The results of the study show that the use of information technology in drilling well mapping can produce more systematic data on the distribution of wells, technical conditions, and the level of damage that occurs. This data is then packaged in the form of a web-based digital map that can be accessed online through the blogger platform. The existence of this digital map makes it easier for local governments to maintain and repair damaged drilled wells. In addition, this mapping also contributes to more targeted policy making related to groundwater management. This innovation is expected to be a sustainable solution in meeting the needs of clean water and improving the quality of public services in Tasikmalaya Regency.